Study on dissolution behavior of saccharin in one molecule of ethanol solvent using molecular dynamic simulation: article - Izauddin, Nur Izwana; Othman, Muhamad Fitri (2019)
Saccharin is a Food and Drug Administration (FDA)-approved sweetener and the most popular used as co former in producing new pharmaceutical co-crystal for the development of drug. The Molecular Dynamic (MD) method was applied to analyze the behavior of five main Saccharin crystal facets with one molecule of ethanol; (1 0 0), (1 1 0), (1 0 2), (1 1 -1), (0 1 1). The interaction of each molecule in one unit cell of the crystal was then analyzed based on Radial Distribution Function (RDF) graph and the dissolution behavior was determined by Mean Square Displacement (MSD) graph. For the RDF analysis, the highest peak of g(r) for the facet (1 0 0), (1 1 0), (1 0 -2), (1 1 -1) are from the molecules 2 at the radius of 5.91, 5.53, 5.41 and 5.19 Å respectively while for the facet (0 1 1), the highest peak was molecule 4 (SAC m4) at radius of 4.95 Å and the interactions are mainly caused by the Coulomb and Van Der Waals.